Design, Technologies and Applications of High Power Vacuum Electronic Devices from Microwave to THz Band - Glyavin, Mikhail (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The last decade has contributed to the rapid progress in developing high-power microwave sources. This Special Issue aims to bring together information about the most striking theoretical and experimental results, new trends in development, remarkable modern applications, new demands in parameter enhancement, and future goals. Although only a tiny part of the achievements of recent years is included in this Issue, we hope that the presented articles will be useful for experts and students focusing on modern vacuum electronics.